A Coupled Method of Laplace Transform and Legendre Wavelets for Lane-Emden-Type Differential Equations. (19th November 2012) - Yin, Fukang; Song, Junqiang; Lu, Fengshun; Leng, Hongze
Abstract : A coupled method of Laplace transform and Legendre wavelets is presented to obtain exact solutions of Lane-Emden-type equations. By employing properties of Laplace transform, a new operator is first introduced and then its Legendre wavelets operational matrix is derived to convert the Lane-Emden equations into a system of algebraic equations. Block pulse functions are used to calculate the Legendre wavelets coefficient matrices of the nonlinear terms. The results show that the proposed method is very effective and easy to implement.